Genetic characterization and passage instability of a novel hybrid virulence plasmid in a ST23 hypervirulent Klebsiella pneumoniae - Fan, Lin-Ping; Yu, Yang; Huang, Shanshan; Liao, Wenjian; Huang, Qi-Sen; Du, Fang-Ling; Xiang, Tian-xin; Wei, Dan Dan; Wan, La-Gen; Zhang, Wei; Liu, Yang (Frontiers in Cellular and Infection Microbiology, 2022)
Hypervirulent variants of Klebsiella pnuemoniae (hvKP), which causes life-threatening infections, is a global priority pathogen and frequently harbours virulence plasmids. The virulence plasmids have emerged as the predominant vehicles carrying the major pathogenic determinants of hypermucoviscosity and hypervirulence phenotypes. In the present study, we characterized a novel virulence plasmid in AP8555, an ST23 hvKP strain, which induced a metastatic infection and fatal septic shock in a critically ill patient. The serum killing assay, the quantitative biofilm formation assay, the G.mellonella infection model, and the mouse lethality assay demonstrated that AP8555 was almost as virulent as the hvKP strain NUTH-K2044. The plasmid pAP855 could be conjugated to Klebsiella quasipneumoniae ATCC700603 and E. coli J53 at a frequency of 7.2× 10−5 and 8.7× 10−7, respectively. Whole-genome sequencing and bioinformatics analysis confirmed that the plasmid was novel, clustered to the incompatibility type of IncHI1B/IncFIB/IncFII and presented high similarity to the pK2044 plasmid. In contrast, a 130-kb large-fragment insertion was observed on the plasmid, which introduced a genetic hybrid zone with multiple conjugation-related genes of type IV secretion systems (T4SS) and CcdAB toxin-antitoxin systems (TAS) to the plasmid. In the transconjugants, the presence of pAP855 had a negative impact on bacterial fitness, but enhancing the virulence-associated phenotypes. In vitro evolution experiments showed that pAP855 in the transconjugants could not be stably inherited after 10 days of passage. Our study not only reports a novel hybrid plasmid but also highlights the putative pathway of conjugative virulence plasmid formation and evolution by means of genetic rearrangement through sequence insertion. These findings indicate that structural versatility could contribute to the dissemination of cointegrate virulence plasmid, although the plasmid incurred a fitness cost. Therefore, continuous monitoring the acquisition of conjugative virulence plasmids may have critical value for plasmid research and increase awareness of hvKP.